Risk factors for development of lameness in gestating sows within the first days after moving to group housing. (February 2017) - Pluym, Liesbet M.; Maes, Dominiek; Van Weyenberg, Stephanie; Van Nuffel, Annelies
Highlights: The incidence of lameness in sows was determined within the first few days of group housing. Associated herd and sow level risk factors were identified. Lameness developed in 13.1% of sows within the first 3–5 days of group housing. Increasing floor space from 1.7 m 2 to 3.0 m 2 decreased the odds of development of lameness in group housed sows. Faecal soiling on the body increased the odds and might be a proxy indicator of lameness. Abstract: Lameness in sows is an important welfare issue that is affected by housing conditions and is thought to be influenced by hierarchical fights within the first days after mixing sows in groups. A longitudinal study in 15 randomly selected herds was performed to investigate the incidence of sow lameness and possible risk factors within the first days of group housing. Each herd was visited just before and again 3–5 days after the sows were moved to group housing. The floor characteristics and dimensions of the group housing facilities were assessed. Locomotion ability, body condition, skin lesions and degree of faecal soiling were recorded for all sows. Additional information on housing and management was obtained using a questionnaire. Amongst the 810 sows included in the study, the mean lameness incidence was 13.1% (95% confidence interval 10.9–15.6%). Following binomial logistic regression analysis, sows with >10% of the body covered with faeces had an increased risk for development of lameness (odds ratio, OR = 2.33, P  = 0.001). An increase in space allowance from 1.7 m 2 to 3.0 m 2 (OR = 0.40, P  = 0.03) and of herd size from 144 to 750 sows per herd (OR = 0.71, P  = 0.02) decreased the risk of development of lameness. Neither the degree of aggression, indicated by skin lesions, nor the floor characteristics influenced the development of lameness. These results indicate that sows can benefit from a larger floor area.